Evaluation of carbon analyzers catalyzers: a study of its effects in water environmental monitoring - Guilherme Faht; Adilson Pinheiro; Marcos Rivail Silva; Diogo Fiamoncini (Revista Ambiente & Água, 2010)
This study evaluated the performance of two carbon analyzer catalyzers, one with high sensitivity and another with regular sensitivity, used in the determination of carbon concentration in a total organic carbon analyzer – TOC. Its applicability was then evaluated in an environmental monitoring study. They have been constructed two calibration curves with 5 points each, first in the interval of 2 mgL-1 at 10 mgL-1 and the second in the interval of 10 mgL-1 at 100 mgL-1. Both calibration curves showed a high level of linearity that can be observed by R2 values that were 0.9996 for the concentration range of 2 mgL-1 to 10 mgL-1, 0.9999 for the concentration range of 10 mgL-1 to 100 mgL-1, and 0.9999 for the concentration range of 100 mgL-1 to 1.000 mgL-1. The limits of detection and quantification for inorganic carbon were, respectively, 0.003 mgL-1 and 0.009 mgL-1. The limits of detection and quantification for the different catalyzers were also evaluated and showed the following values: regular sensitivity: 0.015 mgL-1 and 0.050 mgL-1, respectively, and high sensitivity; 0.004 mgL-1 and 0.013 mgL-1, respectively. The environmental monitoring was performed in two points (PB1 and PB2) in the Garcia stream. Carbon concentrations were monitored during 24 hours with 2-hour intervals between sampling. It was observed that the concentrations of carbon remained constant throughout the experiment, with the exception of the period between 10:00 am and 04:00 pm, probably due to the input of carbonates and bicarbonates derived from textile companies in the region or still had to the launching of urban sewers. Comparing the average carbon concentration, values of point PB2 were always higher than those observed at point PB1. In high concentration analysis, only irrelevant variations were observed with the use of both catalyzers.